2015
DOI: 10.1039/c4ra13460e
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytocompatibility and blood compatibility of polysulfone blend, surface-modified polysulfone and polyacrylonitrile membranes for hemodialysis

Abstract: Three different formulations of dialysis grade membranes and their physiological, cyto- and hemocompatibility have been presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 46 publications
4
29
0
Order By: Relevance
“…Moreover, A3 demonstrated greater thromboresistance than A1 or A2 (Figure 2), suggesting that hydrophilicity and thromboresistance are directly related. Our observations are similar to other those of other researchers, who have demonstrated a decrease in protein adsorption [8][9][10][11]33] and platelet activation with an increase in material hydrophilicity. Our observations are similar to other those of other researchers, who have demonstrated a decrease in protein adsorption [8][9][10][11]33] and platelet activation with an increase in material hydrophilicity.…”
Section: Clotting Time Measurementsupporting
confidence: 92%
“…Moreover, A3 demonstrated greater thromboresistance than A1 or A2 (Figure 2), suggesting that hydrophilicity and thromboresistance are directly related. Our observations are similar to other those of other researchers, who have demonstrated a decrease in protein adsorption [8][9][10][11]33] and platelet activation with an increase in material hydrophilicity. Our observations are similar to other those of other researchers, who have demonstrated a decrease in protein adsorption [8][9][10][11]33] and platelet activation with an increase in material hydrophilicity.…”
Section: Clotting Time Measurementsupporting
confidence: 92%
“…Zavastin et al 31 reported the successful application of PU/CA blend membranes in wastewater treatment in the textile industry. [34][35][36] In addition, better antifouling and antithrombotic properties using PES/PU composite membranes during dialysis was carried out by Yin et al 37 A recent report by Roy et al 38 showed that a PSF/PVP/PEG blend membrane was found to have adequate cyctocompatibility and blood compatibility for hemodialysis. The ux and protein rejection were increased for the blend ultraltration (UF) membranes with dimethylacetamide (DMAc) when compared to dimethylformamide (DMF) as a solvent.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the problem of initial fouling different approaches for surface hydrophilization have been investigated such as copolymerization or grafting with hydrophilic monomers [8][9][10][11][12][13][14], blending using hydrophilic polymers [15][16][17][18][19][20], and, finally, chemical modification of the membrane polymer [21].…”
Section: Polymers 2015 7mentioning
confidence: 99%